Des acteurs étatiques : Léviathan en Amérique - Zylberberg, Jacques (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
This paper deals with the internal dynamics of the Latin American States. Having identified the demographic changes - urbanization, rejuvenating process, widespread education — the author introduces the social changes which have caused the spreading to the masses, to social segmentation and individualization. This is followed by a study of the ideologies which relate the social orientations of the individuals or segmented groups with the overall representations which value authoritarianism, populism, nationalism and state socialism. The analysis of authoritarian ideologies, of social individualism, and of the fragmentized political rivalries validates the internal hypothesis according to which the state actors of Latin America operate with considerable autonomy on the international scène as compared to the other actors.